1980
DOI: 10.3109/10799898009038789
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 0-Alkylated Analogues of Lysine Vasopressin on Adenylate Cyclase of Pig Kidney Membranes

Abstract: O-alkylated analogues (ethyl, propyl, butyl, tert.-butyl) of lysine vasopressin (LVP) and deamino-LVP are partial agonists to LVP in their effect upon activation of adenylate cyclase in porcine kidney membranes. Emax and pD2 values are linearly dependent and both of them are inversely proportional to the overall hydrophobicity of the peptides, expressed in terms of capacity factors in reversed phase high performance liquid chromatography. It is suggested that the increasing hydrophobicity augments the tendency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1986
1986
1996
1996

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…The peptides were chromatographed on a 4 x 250 mm Ultrapac column (LKB, Sweden) filled with Lichrosorb RP8 (10 µ ), using a linear 13.5-34.5% gradient of acetonitrile with 0.1% trifluoroacetic acid (flow rate 1 ml/min). The relative lipophilicity of the peptides was estimated from the retention time on the column as described by Lindeberg et al (1980).…”
Section: Measurement Of Lipophilicitymentioning
confidence: 99%
“…The peptides were chromatographed on a 4 x 250 mm Ultrapac column (LKB, Sweden) filled with Lichrosorb RP8 (10 µ ), using a linear 13.5-34.5% gradient of acetonitrile with 0.1% trifluoroacetic acid (flow rate 1 ml/min). The relative lipophilicity of the peptides was estimated from the retention time on the column as described by Lindeberg et al (1980).…”
Section: Measurement Of Lipophilicitymentioning
confidence: 99%
“…The relative lipophilicity of the peptides was estimated from the retention times on the column and expressed as a lipophilicity constant (log ) (Lindeberg, Vilhardt, Larsson et al 1980). , the capacity constant, was estimated as Vp/Vs -r 1 (Vp is the retention volume for the peptide and Vs that for the solvent).…”
Section: Measurement Of Lipophilicitymentioning
confidence: 99%
“…To test the importance of receptor binding for inhibitory potency, we have measured receptor-binding affinity of a number of oxytocin inhi¬ bitors and compared the results with the antagonistic potency of the peptides. It has previously been shown that activation of adenylate cyclase of isolated kidney membranes by O-alkylated analogues of vasopressin was related to the hydrophilicity of the molecules (Lindeberg, Vilhardt, Larsson et al 1980). Since access and binding of the analogues to the receptor might thus depend on the lipophilicity of the mole¬ cules, this parameter was also measured and corre¬ lated with receptor-binding affinity and antagonistic potency.…”
Section: Introductionmentioning
confidence: 98%